2012
DOI: 10.1186/1471-2296-13-35
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a cognitive behavioral intervention in patients with medically unexplained symptoms: cluster randomized trial

Abstract: BackgroundMedically unexplained symptoms are an important mental health problem in primary care and generate a high cost in health services.Cognitive behavioral therapy and psychodynamic therapy have proven effective in these patients. However, there are few studies on the effectiveness of psychosocial interventions by primary health care. The project aims to determine whether a cognitive-behavioral group intervention in patients with medically unexplained symptoms, is more effective than routine clinical prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The ITT analyses showed that at 12 months, the intervention resulted in a clinically meaningful change in patients’ mental QoL [59,60,61] without improving physical QoL. Among the SF-36 domains, vitality, emotional role functioning and general health perceptions were significantly improved at 12 months.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The ITT analyses showed that at 12 months, the intervention resulted in a clinically meaningful change in patients’ mental QoL [59,60,61] without improving physical QoL. Among the SF-36 domains, vitality, emotional role functioning and general health perceptions were significantly improved at 12 months.…”
Section: Discussionmentioning
confidence: 95%
“…The between-group ES for the MCS was 0.31 in the ITT analysis and 0.37 in the PP analysis. With regard to clinical change, 55% of patients in the treatment group versus 34% in the control group improved by 4 or more points on the MCS (odds ratio 2.27, 95% confidence interval 1.19–4.34; number needed to treat = 4.8), which has been used to determine the clinical change in MUS in primary care [59,60,61]. Regarding the SF-36 domains at 12 months, further ITT analyses showed between-group effects among the SF-36 mental domains of vitality (p = 0.012) and emotional role functioning (p = 0.021) and among the SF-36 physical domain of general health perceptions (p = 0.020; online supplementary table A, www.karger.com?doi=10.1159/000343652).…”
Section: Resultsmentioning
confidence: 99%
“…Bu hasta grubunda en yaygın terapiler davranışçı ve bilişsel-davranışçı tedaviler, farkındalık yaratma ve psikoeğitimdir. [89][90][91][92][93] …”
Section: Tedavide Genel İlkelerunclassified